Regulatory T cell frequency in patients with melanoma with different disease stage and course, and modulating effects of high-dose interferon-α 2b treatment - Ascierto Paolo A; Napolitano Maria; Celentano Egidio; Simeone Ester; Gentilcore Giusy; Daponte Antonio; Capone Mariaelena; Caracò Corrado; Calemma Rosa; Beneduce Gerardo; Cerrone Margherita; De Rosa Vincenzo; et al. (Journal of Translational Medicine, 2010)
Abstract Background High-dose interferon-alpha 2b (IFN-α 2b) is the only approved systemic therapy in the United States for the adjuvant treatment of melanoma. The study objective was to explore the immunomodulatory mechanism of action for IFN-α 2b by measuring serum regulatory T cell (Treg), serum transforming growth factor-β (TGF-β), interleukin (IL)-10, and autoantibody levels in patients with melanoma treated with the induction phase of the high-dose IFN-α 2b regimen. Methods Patients with melanoma received IFN-α 2b administered intravenously (20 MU/m2 each day from day 1 to day 5 for 4 consecutive weeks). Serum Treg levels were measured as whole lymphocytes in CD4+ cells using flow cytometry while TGF-β, IL-10, and autoantibody levels were measured using enzyme-linked immunosorbent assays. Results Twenty-two patients with melanoma received IFN-α 2b treatment and were evaluated for Treg levels. Before treatment, Treg levels were significantly higher in patients with melanoma when compared with data from 20 healthy subjects (P = 0.001; Mann-Whitney test). Although a trend for reduction of Treg levels following IFN-α 2b treatment was observed (average decrease 0.29% per week), statistical significance was not achieved. Subgroup analyses indicated higher baseline Treg levels for stage III versus IV disease (P = 0.082), early recurrence versus no recurrence (P = 0.017), deceased versus surviving patients (P = 0.021), and preoperative neoadjuvant versus postoperative adjuvant treatment groups (not significant). No significant effects were observed on the levels of TGF-β, IL-10, and autoantibodies in patients with melanoma treated with IFN-α 2b. Conclusions Patients with melanoma in this study showed increased basal levels of Treg that may be relevant to their disease and its progression. Treg levels shifted in patients with melanoma treated with IFN-α 2b, although no firm conclusions regarding the role of Tregs as a marker of treatment response or outcome can be made at present.